The demand for medical male circumcision - Chinkhumba, Jobiba; Godlonton, Susan; Thornton, Rebecca L. (American Economic Association, 2014)
This paper measures the demand for adult medical male circumcision using an experiment that randomly offered varying-priced subsidies and comprehensive information to 1,600 uncircumcised men in urban Malawi. We find low demand for male circumcision: only 3 percent are circumcised over a three month period. Despite the low overall level of take-up, both price and information are significant determinants of circumcision. Still, the main barriers to male circumcision—cultural norms and fear of pain—are not affected by prices or information. Significant demand generation efforts are needed for this HIV prevention strategy to be effective. (JEL I11, I18, O15, Z13)